MENINGKATKAN KEMAMPUAN BERHITUNG PERKALIAN MELALUI MEDIA BOARD GAME GOAL TRACKER MAP PADA SISWA KELAS III SD - Femi Br Ginting; Afifa Suci Nahara (STKIP Subang, 2026)
The low multiplication arithmetic ability of third-grade students at SDN 121/I Muara Singoan was the background of this study. Only 35.71% of students achieved the Minimum Completeness Criteria (KKM) in the initial conditions, with an average score of 56.43. This study aims to improve multiplication arithmetic ability through the use of the Goal tracker map board game media. The study employed a Classroom Action Research (CAR) approach using the Kemmis and McTaggart model with 14 third-grade students as subjects. Data were collected through written tests (pre-test and post-test), student and teacher activity observation sheets, and interviews. The results showed that after Cycle I intervention, all students (100%) achieved the KKM with an average score of 86.43—an increase of 30 points from the initial condition. Student activity improved dramatically from the